Parental Leadership in Educational Mobility Decisions: How Indonesian Parents Lead Family Choices for European Higher Education (Germany–France) - Ardin Sianipar; Fransiska Wahyu Ari Susilawati (Universitas Pelita Harapan, 2026)
This systematic review examines how parental leadership influences Indonesian families' decisions to pursue higher education in Europe, specifically in Germany and France. Following PRISMA (2020) guidelines and assessed with MMAT (2022), we reviewed multidisciplinary databases and included 67 studies. We synthesize evidence across five mechanisms to propose and evaluate a sequential pathway: (1) autonomy-supportive parental leadership encourages (2) student participation and agency, which enhances (3) decision quality and satisfaction, enabling (4) pre-departure readiness, and predicting (5) early academic and sociocultural adjustment. Three links—leadership to agency, agency to decision quality, and decision quality to preparedness—are consistently supported, while preparedness to adjustment depends on boundary conditions. Two key moderators are identified: (a) advising and information quality (clarity, credibility, task–fit) strengthens the link from agency to decision quality; (b) cultural and linguistic capital (prior exposure, host-language proficiency) enhances preparedness and sociocultural adjustment. Germany–France policy requirements (e.g., language thresholds, administrative steps, financial documentation) highlight the importance of structured counseling and family role-sharing. The review connects parental leadership theory with family decision-making and study-abroad research, reframing decision quality as justified choice and positioning preparedness as the mechanism driving outcomes. We propose a Family Leadership Playbook and advising protocols (including quality gates, pre-departure sprints, and ERP/CRM tracking). Future research should test dyadic (parent–child) and longitudinal designs, standardize indicators, and incorporate digital traces to identify families at risk.